Peningkatan Motivasi Siswa dalam Pembelajaran Bahasa Arab Melalui Penerapan Metode Edutainment - Isma Fauziyah; Isop Syafei (Yayasan Haiah Nusratul Islam, Indonesia, 2024)
Motivation is essential for the success of Arabic language learning, as students' internal drive affects their engagement and effort in understanding the material. However, enhancing this motivation can be challenging. The edutainment method is considered a potential solution to improve student motivation in learning Arabic. This study aims to increase motivation through the edutainment method at Al-Mu'izz Islamic Elementary School in Bandung. Using a quantitative approach, data were collected through observation, achievement tests, and documentation. The findings show that the edutainment method significantly impacts the motivation of fifth-grade students at Al-Mu'izz Islamic Elementary School. The average pretest score was 47.22, while the posttest score was 84.00, demonstrating a clear improvement. The difference is further confirmed by the t-test result, which shows a significance value of 0.001, less than 0.05. Therefore, it can be concluded that the edutainment method significantly enhances student motivation in Arabic learning at this school.